PENGEMBANGAN DAN VALIDASI METODE KROMATOGRAFI LAPIS TIPIS DENSITOMETRI UNTUK PENETAPAN KADAR TEOFILIN DAN EFEDRIN HIDROKLORIDA SECARA SIMULTAN PADA SEDIAAN TABLET - Lestyo Wulandari; Yuni Retnaningtyas; Diyanul Mustafidah (Research Center for Chemistry - LIPI, 2013)
The combination of Theophylline and Ephedrine isoften used to induce an additive effect in alleviating thesymptoms of respiratory disorders. This research is aimed todevelop a Thin Layer Chromatography (TLC) densitometrymethodfor the simultaneous determination of Theophyllineand Ephedrine hydrochloride in tablet dosage form. Themethod employed TLC aluminium plates precoated withsilica gel 60F254 as the stationary phase and the mixture ofethyl acetate: glacial acetic acid: aquabidest (11: 5 : 1 v/v)asthe eluen system. For detection of Ephedrinehydrochloride, the TLC plate must be re-eluted with 0,5%ninhydrin solution in aquabidest, and then heated at 105Â°Cfor 15 min. Quantitative evaluation was performed bymeasuring the absorbance-reflectance of the analyte spot at279 nm and 505 nm for Theophylline and Ephedrinehydrochloride, respectively. validation of the method showthat TLC Densitometryis selective and specific,showed agood linearity, precise, and accurate and can be used forroutine analysis of tablet in industrial quality controllaboratories.Keywords:TLCDensitometryV, alidationT, heophyllineE, phedrinehydrochloride